Analisis Hubungan Kualitas Tanah Terhadap Produksi Tambak di Pulau Mangkudulis Kabupaten Tana Tidung, Provinsi Kalimantan Utara - Rukisah, Rukisah; Sukardi, Sukardi; Lembang, Miska Sanda; Hutapea, Tri Paus Hasiholan (Jurnal Sumberdaya Akuatik Indopasifik, 2025)
Mangkudulis Island is one of the regions in the Tana Tidung Regency, North Kalimantan Province, which has significant potential in fisheries, particularly traditional shrimp pond aquaculture for tiger shrimp (Penaeus monodon). In general, environmental factors, such as soil quality, will affect the quality of pond water. The issue of water quality in shrimp ponds generally begins with soil quality, including pH, redox potential, organic carbon content, total nitrogen, C/N ratio, Fe, Mn, Al, and soil texture. This study aims to analyze soil quality parameters in relation to tiger shrimp pond production. The research was conducted over two months, from August to September 2022, in the tiger shrimp ponds on Mangkudulis Island. Soil samples were analyzed in a laboratory for parameters such as pH, redox potential, organic matter, texture, and heavy metals. The results of the soil quality measurements from Mangkudulis Island shrimp ponds indicate that the soil quality, based on parameters such as pH, redox potential, organic matter, and texture, does not meet the standard quality criteria. However, the levels of heavy metals (Al, Fe, and Mn) are within the acceptable standards. The average results for each parameter were: pH 5.5, redox potential -293 mV, organic carbon 2.26%, total nitrogen 0.18%, C/N ratio 13.15, sand 12.20%, silt 52.72%, clay 35.08%, Al 11.14 ppm, Fe 36.26 ppm, and Mn 17.42 ppm. These results were compared with shrimp production data obtained through interviews with pond owners. The average pond production is 300 kg/hectare, with 70,000 seed shrimp stocked at a density of 40 shrimp per kg. This result is not optimal due to the soil quality in the Mangkudulis ponds. Proper soil management needs to be implemented before the ponds are reused.